2022
DOI: 10.3390/ijms231710129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of the Fibroblast Growth Factor Type 2 (FGF-2) Administration on Placental Gene Expression in a Murine Model of Preeclampsia Induced by L-NAME

Abstract: The abnormal implantation of the trophoblast during the first trimester of pregnancy precedes the appearance of the clinical manifestations of preeclampsia (PE), which is a hypertensive disorder of pregnancy. In a previous study, which was carried out in a murine model of PE that was induced by NG-nitro-L-arginine methyl ester (L-NAME), we observed that the intravenous administration of fibroblast growth factor 2 (FGF2) had a hypotensive effect, improved the placental weight gain and attenuated the fetal growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…First, the researchers studied the Wnt and MAPK signaling pathways during the 6–8 weeks of gestation. They identified the basal medium components, including epidermal growth factor (EGF) ( Cheng et al, 2022 ) and fibroblast growth factor 2 (FGF-2) ( Martinez-Fierro et al, 2022 ), and enzymatically digested the placenta during early pregnancy. EpCAM-labeled trophoblast cells, which are a specific subtype of trophoblast cells, were obtained.…”
Section: Trophoblast Organoid Modelsmentioning
confidence: 99%
“…First, the researchers studied the Wnt and MAPK signaling pathways during the 6–8 weeks of gestation. They identified the basal medium components, including epidermal growth factor (EGF) ( Cheng et al, 2022 ) and fibroblast growth factor 2 (FGF-2) ( Martinez-Fierro et al, 2022 ), and enzymatically digested the placenta during early pregnancy. EpCAM-labeled trophoblast cells, which are a specific subtype of trophoblast cells, were obtained.…”
Section: Trophoblast Organoid Modelsmentioning
confidence: 99%
“…Male ethanolexposed placentas displayed altered methylation and/or expression patterns in several genes that are directly linked to embryonic growth restriction. For example, a study recently showed that injecting fibroblast growth factor 2 (Fgf2; downregulated in male ethanol-exposed placentas) into a rat model of preeclampsia improved clinical outcomes, including attenuating fetal growth restriction (Martinez-Fierro et al, 2022). Mutation of Fgf1 (increased methylation in male ethanol-exposed placentas) has been linked to preeclampsia in humans (Marwa et al, 2016), while Bmp6 (decreased methylation in male ethanolexposed placentas) was downregulated in the fetal kidneys of rats with intrauterine growth restriction in a model of induced hypertension due to chronic insulin administration (Bursztyn et al, 2006).…”
Section: 1sex-specific Impacts Of Preimplantation Alcohol Exposure On...mentioning
confidence: 99%
“…Martinez-Fierro et al [ 7 ] present interesting findings on the pathogenesis of preeclampsia, evaluating the effect of the administration of fibroblast growth factor type 2 on the placental expression of various genes involved in angiogenesis and apoptosis in an experimental murine model of preeclampsia. The administration of fibroblast growth factor type 2 reduced the effects generated by proteinuria and hypertension and also impacted the expression of studied genes.…”
mentioning
confidence: 99%